PENGARUH PERTUMBUHAN AKTIVA PRODUKTIF, DANA PIHAK KETIGA, NPL, DAN APLIKASI SIA PADA KINERJA OPERASIONAL LPD - Dewi, Dewa Ayu Paramita; Suartana, I Wayan (E-Jurnal Akuntansi, 2017)
Operational performance measurement needs to be done to determine whether the implementation of the performance is in accordance with the plan or targets that have been formulated. This study aimed to examine the effect of growth in earning assets and deposits, the level of non-performing loans, and accounting information system applications on operating performance Credit Institutions in Gianyar regency period 2013-2015. The population in this study was 270 LPD. The number of samples in this study was 38 LPD in Gianyar using probability sampling technique, stratified random sampling method with formula Slovin. Data analysis technique used is multiple linear regression analysis. The research results are credit growth and NPL have negative effect on operating performance, growth of deposits has a positive effect on operating performance, growth of savings do not affect the operating performance, and application of accounting information system negatively affect the operational performance.
Keywords: loan growth, third party funds, NPL, applications of accounting information system, and operational performance